PENGARUH PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN MAXIM SAMARINDA - Zulkifli Zulkifli; Novandrin Novandrin (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2023)
The large number of online transportation businesses in Samarinda make Maxim have to maintain the quality of their service because service quality is an advantage produced by producers in fulfilling the desires of customers who can make them feel satisfied so that later it will be of benefit to these customers and can come back if a service is provided. very good. With intense competition, service quality must be prioritized because consumers will be more vague about what they receive and what they expect from an online transportation service company. Based on the results of testing the hypothesis on Price, Service Quality simultaneously shows that it is proven to have a positive and significant influence on Maxim Samarinda's Customer Satisfaction. Thus, the hypothesis in this study is accepted. on price shows that it is proven to have a positive and not significant effect on Maxim Samarinda's Customer Satisfaction. Therefore, the hypothesis in this study was rejected. on Service Quality shows that it is proven to have a positive and significant influence on Customer Satisfaction Maxima Samarinda. Thus, the hypothesis in this study is accepted.